Spatial Heterogeneity of Cortical Excitability in Migraine Revealed by Multi-Frequency Neuromagnetic Signals - Xiang, Jing (J Pain, 2016)
To investigate the spatial heterogeneity of cortical excitability in adolescents with migraine, magnetoencephalography (MEG) recordings at a sampling rate of 6000 Hz were obtained from 35 adolescents with an acute migraine and 35 age- and gender-matched healthy controls during an auditory-motor task. Neuromagnetic activation from low- to high-frequency ranges (5–1,000 Hz) was measured at both sensor and source levels. The heterogeneity of cortical excitability was quantified within each functional modality (auditory vs. motor) and hemispherical lateralization. MEG data showed that high-frequency, not low-frequency neuromagnetic signals, revealed heterogeneous cortical activation in migraine subjects as compared with controls (p < 0.001). The alteration of the heterogeneity of cortical excitability in migraine was independent of age and gender. The degree of the neuromagnetic heterogeneity of cortical activation was significantly correlated with headache frequency (r=0.71, p < 0.005). The alteration of cortical excitability in migraine is spatially heterogeneous and frequency dependent, which has not previously been reported. The finding may be critical for developing spatially targeted therapeutic strategies for normalizing cortical excitability with the purpose of reducing headache attacks. PERSPECTIVE: This article presents a new approach to quantitatively measuring the spatial heterogeneity of cortical excitability in adolescents with migraine using MEG signals in a frequency range of 5–1000 Hz. The characteristics of the location and degree of cortical excitability may be critical for spatially targeted treatment for migraine.